Membangun Keimanan dan Toleransi Beragama Melalui Model Pembelajaran Hiwar Jadali di Masa Pandemi Covid-19 - Rahmat, Munawar; Firdaus, Endis (Universitas Pendidikan Indonesia, 2020)
Abstract. Religious tolerance among students is quite problematic. The results of previous studies showed that student’s intolerance was quite high. The question is, how to teach students a solid faith and be tolerant of other religions and different Islamic groups? Abdurrahman An-Nahlawi, An Islamic Scholar and Professor of Islamic Education in Egypt introduced seven types of Quranic methods, one of which is Hiwar Jadalī (dialogue-argumentative Qurani). This method is thought to strengthen faith as well as religious tolerance of students, provided that the lecturer can choose the right verses. This study aims to produce Hiwar Jadalī learning model in Islamic Religious Education to strengthen the religious belief and tolerance of UPI students. This research uses descriptive-comparative method. Two classes used the Hiwar Jadalī learning model while the other two classes used the ordinary model. As a result, Hiwar Jadalī’s learning model was proven to be more effective in strengthening students’ faith and religious tolerance. Abstrak. Toleransi beragama di kalangan mahasiswa cukup bermasalah. Hasil-hasil penelitian terdahulu menunjukkan intoleransi mahasiswa cukup tinggi. Pertanyaannya, bagaimanakah mengajarkan keimanan yang kokoh kepada mahasiswa sekaligus toleran terhadap agama dan golongan Islam lain yang berbeda?. Abdurrahman An-Nahlawi, Ulama dan Guru Besar Pendidikan Islam Mesir mengenalkan tujuh jenis metode Qurani, salah satunya Hiwar Jadalī (dialog-argumentatif Qurani). Metode ini diduga dapat mengokohkan keimanan sekaligus toleransi beragama bagi mahasiswa, dengan catatan dosen dapat memilih penggalan ayat-ayat yang tepat. Penelitian ini bertujuan menghasilkan model pembelajaran Hiwar Jadalī dalam Pendidikan Agama Islam untuk mengokohkan keimanan dan toleransi beragama mahasiswa UPI. Penelitian ini menggunakan metode deskriptif-komparatif. Dua kelas menggunakan model pembelajaran Hiwar Jadalī sedangkan dua kelas lainnya menggunakan model biasa. Hasilnya, model pembelajaran Hiwar Jadalī terbukti lebih efektif mengokohkan keimanan dan toleransi beragama mahasiswa.